The impact of credit rating changes on CEO turnover. - Foo, Wei Ling. (2013)
In an effort to contribute to the literature regarding credit ratings’ effects on corporate governance theories, this study examines the impact of credit rating changes on one particular aspect of corporate governance: CEO turnover in North America. Our data set consists of firms in the S&P Composite 1500 index from the period of 1992 to 2010, which we filtered, winsorised and regressed to seek answers for the research objectives and our results show that credit rating changes do affect CEO turnover; specifically, a worsening of credit ratings leads to increased CEO turnover. We attribute this finding to the fact that credit ratings are used as an evaluation tool for CEO performance: a credit rating upgrade indicates good management and the CEO may hence be rewarded; conversely, credit ratings downgrades may indicate incompetency and the CEO is punished by forced turnover.